Administrative Supervision of Work of Port Authorities in the Republic of Croatia - Vojković, Goran (Promet - Traffic&Transportation)
Administrative supervision is one way of holding controlover administration and legal persons who have certain publicauthorities when performing their function, one of such beingthe Port Authority. Perfonning public authorities - concerningthe fact that it is a fonn of public power - must be under legalsupervision of the state and its bodies. The Act on MaritimeDomain and Sea Ports as well as the Act on Inland Ports, eachin its particular area, foresee the possibility of performing administrationsupervision over port authorities work. This is a legallyand functionally extremely interesting fonn of supervision;administration supervision is not brought up for the reason ofperfonning some internal police function that shows up once ina while only if there are some difficulties in work. Administrationsupervision must be continuous and provide assistance tobodies over which the supervision is held. This paper analyseslegal grounds and potential fonns of administration supervisionover the work of port authorities.